2023
DOI: 10.1002/adsc.202201253
|View full text |Cite
|
Sign up to set email alerts
|

B−N Coordinated Phenanthroimidazole‐Based Zinc‐Salen as a Photocatalyst for the Synthesis of Oxazolidinones using Carbon Dioxide as a C1 Source under Mild Reaction Conditions

Abstract: Cycloaddition of carbon dioxide (CO2) with aziridine catalyzed by a zinc‐salen having B−N coordinated phenanthroimidazole motif as a photocatalyst (1), at 1 bar CO2 pressure and room temperature under solvent free condition is presented. The photocatalyst exhibited excellent selectivity and tolerates a variety of substituted aziridines, and successfully produces the corresponding oxazolidinones at mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 80 publications
0
1
0
Order By: Relevance
“…64 Recently, Venkatasubbaiah et al described the solvent-free reaction of aziridines ( 212 ) and carbon dioxide ( 204 ), catalyzed by a zinc-salen having a B–N coordinated phenanthroimidazole motif ( 213 ) as a photocatalyst, for the synthesis of oxazolidinones ( 214 ) (Scheme 38 – path c). 65…”
Section: Reactions Of Aziridinesmentioning
confidence: 99%
“…64 Recently, Venkatasubbaiah et al described the solvent-free reaction of aziridines ( 212 ) and carbon dioxide ( 204 ), catalyzed by a zinc-salen having a B–N coordinated phenanthroimidazole motif ( 213 ) as a photocatalyst, for the synthesis of oxazolidinones ( 214 ) (Scheme 38 – path c). 65…”
Section: Reactions Of Aziridinesmentioning
confidence: 99%
“…20−52 Despite the discovery of various four-coordinated boron materials, B−N-coordinated materials have gained significant interest due to their propensity to form a planar conformation and their rigid structure, which enhance the materials' electron-accepting capacity. 25,28,29,34,38,40,41,45,47,48,50,52−54 As a result of their intriguing characteristics, B−N-tetra-coordinated molecules find application as oxygen sensors, 41 photocatalysts, 50,52 photochromic materials, 38 and so on.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Because of their conceivable usage in organic field-effect transistors, organic photovoltaics, and organic light-emitting diodes, conjugated polycyclic aromatic hydrocarbons, or PAHs, have gained popularity. The reduced highest occupied molecular orbital–lowest unoccupied molecular orbital (HOMO–LUMO) gap exhibited by PAHs has proven valuable for developing materials used in optoelectronic applications, as discussed vide supra . In recent studies, it has been shown that the electronic properties of PAHs can be altered by incorporating main-group elements such as N, Si, B, P, and S into their backbone. PAHs embedded with main-group elements, especially, PAHs with tri- and tetra-coordinated boron compounds exhibited tunable properties such as phosphorescence, thermally induced delayed fluorescence, and strong fluorescence. Despite the discovery of various four-coordinated boron materials, B–N-coordinated materials have gained significant interest due to their propensity to form a planar conformation and their rigid structure, which enhance the materials’ electron-accepting capacity. ,,,,,,,,,,, As a result of their intriguing characteristics, B–N-tetra-coordinated molecules find application as oxygen sensors, photocatalysts, , photochromic materials, and so on.…”
Section: Introductionmentioning
confidence: 99%